The impact of stock liquidity on stock price crash risk: Empirical research on listed firms in Vietnam - Manh, Pham Tien; Linh, Nguyen Do Tue; Linh, Nguyen Ngoc Phuong (Asian Journal of Economic Modelling, 2025)
Vietnam's stock market is now highly developed and significant to the economy of the country. Many previous researches have studied the factors that affect stock prices on the stock market. Therefore, in this article, the authors examine the impact of stock liquidity on stock price crash risk with a sample space of companies on the Ho Chi Minh City Stock Exchange (HOSE) from 2016 to 2022. By using the linear regression research model, the authors found that stock liquidity has a negative impact on stock price crash risk. In this model, stock price crash risk will be the dependent variable, whereas stock liquidity will be the explanatory variable, which will ultimately determine the accuracy and suitability of the model through observed data. This topic provides considerable value to the depth of knowledge on stock liquidity and stock price crash risk in emerging markets and is helpful for emerging markets to monitor stock liquidity there. Additionally, this study offers potential strategies to manage stock price crash risk, which is valuable information for investors, authorities, regulators, and policymakers.